COGNITIVE IMPAIRMENT IN DIFFERENT CLINICAL FORMS OF MULTIPLE SCLEROSIS - Behidzhe Sadarzanska-Terzieva; Silvia Tsvetkova (Peytchinski Publishing, 2024)
Purpose: The aim of the study is to investigate cognitive impairment (CI) in patients with different clinical forms of Multiple Sclerosis (MS) and to propose a suitable cognitive evaluation based on available tools for diagnosis and monitoring purposes. Materials and Methods: The following tests were used: Paced Auditory Serial Addition Test (PASAT), Symbol Digit Modalities Test (SDMT), Brief Visuospatial Memory Test-Revised (BVMT-R), Expanded Disability Status Scale (EDSS) and Magnetic Resonance Tomography 1.5Т (МRТ) in 60 consecutive patients; 22 were with first demyelination episode and 38 with MS. The control group of 40 healthy persons matched for sex, age and years of education. The follow-up period is three years. Results: The average screening values of PASAT, SDMT, BVSMT-R are considerably lower (р<0.05) in MS patients compared to the controls and CIS patients. Point's number in the progressive forms in comparison with RRMS is reliably smaller. There was no significant difference in results between SPMS and PPMS patients at screening (р>0.05). In the 3rd year, there is a significant cognitive progression in all studied groups and for all tests (р<0.05). Conclusion: The use of a neuropsychological screening test is a valuable method for registering CI in patients with relapsing-remitting course, as well as in patients with a progressive course of the disease. We recommend the SDMT for screening annual follow-up because it is easy to apply, validate and reliably report the progression of CI. In patients with visual disturbances and with arm weakness, it is better to use PASAT, taking into account the level of education and depression.